Demosntrativos e o fio do discurso (Revista de Estudos da Linguagem, 1995)
Linguistic as well as phylosophical tradition do not tak:e inta account a discoursive leveI of reference, necessarily ideological, that determines the 'exoforic' or 'anaphoric' deixis. From the analysis ofthe demonstrative pronouns of spoken POrWguese, this work proposes that the demonstrative pronouns, fimctioning either as determiners ar as noun phrases as a whole, constitute a privileged place ofcontact that the discourse event keeps with its specific exterior or with its interdiscoursive domain.